2015
DOI: 10.1007/s00432-015-1991-5
|View full text |Cite
|
Sign up to set email alerts
|

The use of targeted MR-guided prostate biopsy reduces the risk of Gleason upgrading on radical prostatectomy

Abstract: MpMRI and targeted MR-GB are useful tools to better characterize and stage the extent of disease, and therefore enable the urologist to better risk-stratify and counsel the patient. The combined use of targeted MR-GB and TRUS-GB presents the least risk of Gleason underestimation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 36 publications
2
36
0
Order By: Relevance
“…10 Over the past decades, targeted magnetic resonance imagingguided prostate biopsy was developed and has demonstrated their interest in order to reduce the risk of GS upgrading on Low serum testosterone in PCa after RP A Pichon et al RP. 45,46 In pursuing the same objective, clinical-biological parameters were studied. 40,47 Clinically, obesity, prostate weight and the number of positive cores were correlated with the risk of GS underestimation.…”
Section: Discussionmentioning
confidence: 99%
“…10 Over the past decades, targeted magnetic resonance imagingguided prostate biopsy was developed and has demonstrated their interest in order to reduce the risk of GS upgrading on Low serum testosterone in PCa after RP A Pichon et al RP. 45,46 In pursuing the same objective, clinical-biological parameters were studied. 40,47 Clinically, obesity, prostate weight and the number of positive cores were correlated with the risk of GS underestimation.…”
Section: Discussionmentioning
confidence: 99%
“…Arsov et al . demonstrated that combining MRI‐targeted and standard biopsy significantly reduced the risk of Gleason upgrading in RP compared to standard and targeted biopsy used alone (28.8%, 40.4%, and 50.0%, respectively) Siddiqui et al further showed that MRI‐targeted biopsy upgraded and detected PCa of higher GS in 32% of patients compared with standard 12‐core biopsy alone. Targeted biopsy preferentially detects higher‐grade PCa while missing lower‐grade tumors .…”
Section: Magnetic Resonance Imaging (Mri)‐targeted Prostate Biopsiesmentioning
confidence: 99%
“…Lanz et al found that MRI-targeted biopsy allowed for an accurate estimation of GS in more than 2/3 of patients, while GS misclassification was mostly due to a lack of accuracy in the determination of the secondary Gleason grade. 53 Arsov et al demonstrated that combining MRI-targeted and standard biopsy significantly reduced the risk of Gleason upgrading in RP compared to standard and targeted biopsy used alone (28.8%, 40.4%, and 50.0%, respectively) 54 Siddiqui et al further showed that MRI-targeted biopsy upgraded and detected PCa of higher GS in 32% of patients compared with standard 12-core biopsy alone. Targeted biopsy preferentially detects higher-grade PCa while missing lower-grade tumors.…”
Section: Magnetic Resonance Imaging (Mri)-targeted Prostate Biopsiesmentioning
confidence: 99%
“…MR guidance consistently provided excellent soft‐tissue contrast, intrinsic flow sensitivity, multiplanar imaging capabilities, good spatial resolution, near real‐time imaging, and involves no ionizing radiation . The first MR‐guided interventional clinical trials were reported in 1986 .…”
Section: Discussionmentioning
confidence: 99%